Financing for sustainability transformations in disruptive times - Paula von Haaren; Axel Berger; Bambang Brodjonegoro; Lena-Marie Putz (German Institute of Development and Sustainability (IDOS), 2025)
Progress on the Sustainable Development Goals (SDGs) is increasingly hampered by insufficient funding. This Policy Brief, drawing on insights from a roundtable held in the context of the Hamburg Sustainability Conference (HSC) with experts from the Americas, Africa, Europe, and Asia, examines how sustainable development financing can be safeguarded in an era of economic disruptions, global conflicts, and political shifts. It situates these recommendations within the context of the outcomes of the fourth Financing for Development (FfD4) Conference, with a view to informing the follow-up process. An estimated USD 4.2 trillion are needed for the implementation of SDG policies. Notwithstanding this, economic insecurity, slow growth, and waning political commitment reduce private and public investments in sustainability. Rising conflicts lead to a redistribution of budgets towards military expenditures and away from environmental and social objectives. This includes reductions in Official Development Aid, further limiting funding for sustainability transformations in low- and middle-income countries. In order to sustain and increase financing for SDG implementation, taking the challenging framework conditions into account, a series of actions is needed: - Alignment of public spending with the SDGs and planetary boundaries by phasing out harmful subsidies and integrating sustainability into credit ratings and investment strategies. - Strengthening domestic revenue mobilisation through improved and efficient tax systems, tax transparency, and reduction of harmful tax expenditures. - Building institutional capacity in transitioning sectors, including sustainable finance, digitalised tax systems, and data provision for and engagement with credit-rating agencies. - Translating FfD4 outcomes into concrete actions in platforms like the G20, the International Monetary Fund (IMF)/World Bank meetings, and the HSC, aligning them with social and environmental priorities. But also filling the gaps on issues neglected in FfD4 by supporting future multilateral agreements and voluntary initiatives on tax, SDRs, cost of capital, and debt restructuring.
Keywords: 320; financing for development; international cooperation; international financial institutions; sustainability; sustainable development; SDGs; domestic resource mobilisation; official development assistance; debt; taxation